Live integration of comprehensive cardiac CT for myocardial fibrosis and coronary anatomy with electroanatomical mapping in patients with refractory ventricular tachycardia: a pilot study. (20th July 2021) - Conte, E; Carbucicchio, C; Catto, V; Kochi, AN; Mushtaq, S; Sattin, T; De Iuliis, P; Pontone, G; Pepi, M; Tondo, C; Andreini, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Aim of the study was to verify the feasibility and accuracy of live integration of myocardial fibrosis evaluated at CCT with EAM. The present is the first report of live integration of cardiac computed tomography (CCT) data for myocardial fibrosis and coronary anatomy with electroanatomical mapping (EAM). We prospectively enrolled all patients admitted with a clinical indication to endocardial and epicardial EAM before radiofrequency catheter ablation (RFCA) of refractory ventricular tachycardia (VT) and an absolute contraindication to cardiac magnetic resonance. All patients underwent per protocol CCT for myocardial fibrosis and coronary anatomy evaluation, before RFCA procedures. Sensitivity, specificity, negative predictive value, positive predictive value and diagnostic accuracy were assessed for myocardial fibrosis evaluation with CCT vs EAM on a per segment-basis taking into consideration both any type of fibrosis and ischemic vs non ischemic subtypes. Live integration feasibility of CCT vs EAM was evaluated for every patients. Live integration feasibility and diagnostic performance of CCT vs EAM for myocardial fibrosis identification was evaluated for every patients. EAM adverse events were recorded as well. In all patients CCT data were successfully integrated with EAM during RFCA procedure. All patients had myocardial fibrosis correctly identified at CCT vs EAM on a per-patients basis. A diagnostic accuracy of 94.1% for detection of any type of myocardial fibrosis at CCT vs EAM was recorded. No pericardial tamponade and/or pericardial effusion were recorded. CCT identification of myocardial fibrosis is feasible and accurate vs EAM in a very selected high risk patients with clinical indication to RFCA of VT and contraindication to CMR. CCT images integration during EAM is feasible and enable to provide electrophysiologist useful information regarding myocardial fibrosis and coronary arteries location, possibly avoiding invasive coronary angiography.